The Experience of Economic Reforms in Turkey "An Analytical Study" - Tahar BEN KHEIRA (Dirassat Journal Economic Issue, 2024)
The Turkish experience is one of the successful experiences in economic reforms, and one of its fruits is that Turkey made a quantum leap in the path of progress and economic stability, as the Turkish economy became among the strongest economies in the world, and until recently the Turkish economy before 2002 was suffering from internal and external imbalances, the most important of which Declining national product, high external debt, high rates of poverty, unemployment, inflation, low per capita income, trade deficit and balance of payments, in addition to the political and regional conditions, all of these factors contributed to the failure of the multiple economic reforms implemented in Turkey. In this paper, we will try to extrapolate the Turkish experience and the reform policies that Turkey adopted and implemented and succeeded in achieving the most important goals it set, then highlighting the factors and reasons for the success of the Turkish model in embodying economic reforms